(untitled) (Inženierzinātņu un augstskolu vēsture, 2018)
Būvinženieris Voldemārs Bergkinds sāka studijas Rīgas Politehniskajā institūtā, beidza Latvijas Universitāti 1922. gadā. Viņš bija ceļu inženieris Satiksmes ministrijā, bet arī projektēja dažādas jaunceltnes un ēku pārbūves. Vairākas viņa plānotas celtnes saglabājušās Madonā, kur kopš 1928. gada V. Bergkinds bija pilsētas inženieris. Pēc Otrā pasaules kara viņš dzīvoja Austrijā, piedalījās Raiņa un Aspazijas pieminekļa iekārtošanā Šveicē, Kastaņolā.Madona City Engineer Voldemārs Bergkinds (1897–1978)Civil engineer Voldemārs Bergkinds started his studies at the Department of Civil Engineering of Riga Polytechnic Institute and continued at the University of Latvia. In 1922, he received the Diploma of Civil Engineer and was a road engineer with the Ministry of Transport of Latvia. He has developed the design for various new buildings and modifications of the existing ones. Some of the buildings he designed can be seen in Madona. Bergkinds had been the Civil Engineer of the town of Madona since 1928. After World War II, he lived and worked in Austria. He took part in the construction of the monument to Latvian poets Rainis and Aspazija in Castagnola, Lugano, Switzerland. The monument was restored in 1972. Bergkinds died in January 1978 at the age of 80 in Innsbruck, Austria, where he was buried.Keywords: Voldemārs Bergkinds, road construction, building design, Madona, monument to Rainis and Aspazija in Switzerland.Инженер города Мадона Волдемарс Бергкиндс (1897–1978)Инженер-строитель Волдемарс Бергкиндс начал учебу на Инженерном отделении Рижского политехнического института и продолжил в Латвийском университете, где в 1922 году получил диплом. Он работал в качестве инженера-строителя в Министерстве сообщения Латвии, а также разработал целый ряд новых конструкций в процессе реконструкции зданий. С 1928 года В. Бергкиндс работал инженером в городе Мадоне. Несколько зданий, построенных в городе по его проекту, сохранились до наших дней. После Второй мировой войны он жил и работал в Австрии. Он являлся одним из активистов по постройке памятника латышским поэтам Райнису и Аспазии в Кастаньоле, Лугано, Швейцария. Памятник был открыт в 1972 году. Скончался В. Бергкиндс в Инсбруке в январе 1978 года, в возрасте восьмидесяти лет.Ключевые слова: Волдемарс Бергкиндс, дорожное строительство, проектирование зданий, Maдонa, память о Райнисе и Аспазии в Швейцарии.